2022
DOI: 10.3390/machines10030194
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Uneven Lighting on Quantitative Indicators of Surface Defects

Abstract: The impact of the illumination level on the quantitative indicators of mechanical damage of the rolled strip is investigated. To do so, a physical model experiment was conducted in the laboratory. The obtained images of defects at light levels in the range of 2–800 lx were recognized by a neural network model based on the U-net architecture with a decoder based on ResNet152. Two levels of illumination were identified, at which the total area of recognized defects increased: 50 lx and 300 lx. A quantitative ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…The dataset used in this study is obtained from the InfiRay Infrared Open Platform [20], which is an open dataset dedicated to infrared ships. The creation of an infrared dataset requires accurate camera calibration and proper positioning to obtain high-quality and precise infrared images [21]. This dataset is generated through on-site testing and adjustments, employing a fixed position and stable lighting conditions within the same scene.…”
Section: Infrared Ship Datasetmentioning
confidence: 99%
“…The dataset used in this study is obtained from the InfiRay Infrared Open Platform [20], which is an open dataset dedicated to infrared ships. The creation of an infrared dataset requires accurate camera calibration and proper positioning to obtain high-quality and precise infrared images [21]. This dataset is generated through on-site testing and adjustments, employing a fixed position and stable lighting conditions within the same scene.…”
Section: Infrared Ship Datasetmentioning
confidence: 99%
“…Modern investigations showed that neural network-based defect detection methods allow high accuracy to be reached in the recognition of different classes of surface defects [22][23][24]. However, investigating and streamlining neural networks' capabilities and limitations in detecting, classifying, and calculating the parameters of the most common group defects appear crucial [25][26][27].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it is important from the perspective of real-time execution to have a reduction in the size of fusion architectures while maintaining comparable performance [10]. Besides, reduced architectures may have different level of robustness to change in illumination level [11]. Furthermore, this reduction can also be used to extend the perception systems with uncertainty handling methods [12], [13].…”
Section: Introductionmentioning
confidence: 99%